KONSTRUKSI SOSIAL TRADISI BUKA LUWUR SUNAN KUDUS DI DESA KAUMAN KABUPATEN KUDUS JAWA TENGAH (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
Buka Luwur tradition of Sunan Kudus in Kudus City is carried out to commemorate the day of death (the haul) of Sunan Kudus. Buka Luwur tradition is carried out regularly every year with the peak of the event always falling on the 10th of Muharram. Many people of Kudus City are waiting for the ceremony to receive blessings from Sunan Kudus. This study aims to explain the procession of the Buka Luwur tradition and to analyze how the social construction of the Kauman Village community towards the Buka Luwur tradition so that this tradition is passed down from generation to generation. This study uses a qualitative method with an explanatory approach. The theory of social construction by Peter L. Berger is used to analyze the social construction process of the Buka Luwur tradition of the people of Kauman Village. The results of the study show that the social construction of the Buka Luwur tradition carried out by the people of Kauman Village, Kudus City aims to respect and remember the services of Sunan Kudus, who is a highly respected and respected figure in Kudus.